1975
DOI: 10.1136/hrt.37.5.471
|View full text |Cite
|
Sign up to set email alerts
|

Acute inferior wall myocardial infarction associated with complete atrioventricular block and left posterior hemiblock.

Abstract: Three cases of acute inferior wall myocardial infarction associated with complete atrioventricular block and junctional escape rhythm showing left posterior hemiblock are presented. The triad appears to consitiute a distinct syndrome. It is postuated that the subsidiary pacemaker is situated either in the bundle of His or the proximal part of the anterior division of the left bundle-branch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The in-hospital mortality rates and major adverse cardiac events did not differ significantly in patients with and without CAVB. Several studies have shown that patients with inferior MI who are complicated by CAVB had an elevated risk of in-hospital events [ 10 , 11 ]. In one study, CAVB significantly influenced the outcome when associated with right ventricular infarction, leading to high mortality owing to cardiomyopathy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The in-hospital mortality rates and major adverse cardiac events did not differ significantly in patients with and without CAVB. Several studies have shown that patients with inferior MI who are complicated by CAVB had an elevated risk of in-hospital events [ 10 , 11 ]. In one study, CAVB significantly influenced the outcome when associated with right ventricular infarction, leading to high mortality owing to cardiomyopathy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%